Radionuclide Lymphoscintigraphy in the Evaluation of Lower Extremity Lymphedema – Single Hospital Experience - Parveen, Rahima; Begum, Shamim MF; Jabin, Zeenat; Nath, Khokon Kumar (Bangladesh Journal of Nuclear Medicine, 2017)
Objective: To find out the type of pattern of obstruction in patient with lymphedema of lower extremities by Lymphoscintigraphy to evaluate. Method: This retrospective study was carried out at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) from January 2014 to June 2014. The study included 51 patients. Lymphoscintigraphy performed by Tc-99m nano-colloid and were interpreted by expert of Nuclear Medicine Physician. Result: Lymphoscintigraphy was done total 51patients with clinically diagnosed lymphedema (29 males and 22 females; age range 10–80 years). Seventeen patients (33.3%) revealed normal flow in both limbs, whereas only one patients (1.9%) consistent with primary lymphedema. Thirty-three patients (64.7%) consistent with secondary lymphedema, where thirty patients (58.8%) revealed unilateral partial obstruction and three patient (5.9%) had bilateral partial obstruction. Conclusion: Lymphoscintigraphy is safe and effective Bangladesh J. Nuclear Med. 18(1): 43-46, January 2015